Seasonal presence of the two species of white flies Acaudaleyrodes ra-chipora ( Singh ) and Aleurolobus marlatti (QUAN) (Hemip-tera:Aleurodidae)on the christ-thorn Zizyphus spina Christi. - Al-Khafaji, Sahar Muhassin; Tarash, Nawars Wleed (Journal of Kerbala for Agricultural Sciences, 2018)
This study was conducted in the Baghdad university/ college of Agriculture in Al –Jadriya district to determined the population density and infection percentage of the two species of white flies Acaudaleyrodes rachipora (Singh.) and Aleurolobus marlatti( QUAN.) on the Christ-thorn plant during 4/1/2017 to5/5/2017. Results showed that the highest infection for the white fly A. rachipora was 58.88% in the begining of January, while the lowest infection was 24.88% in the late April.Whereas no significant differences were observed among the three levels( top ,middle and lower ) was 36.63% ,39.03% and 41.13% respectively. The highest average of the population density was 5 Nymph/leaf which occurred in the first of January,in the middle part of the plant ,while the top and lower part of the plant, reached 3 and 2 N/L respectively.In the frist of May reduced average to1 N / L . For Whitefly A. marlatti,The highest infection was 65.66 and 72.33 % in the mid of January and February respectively.While,the lowest infection occurred in the first ofApril and May, was 30.88 and 34.44% respectively.The highest average of population density was reached 6 n /l in the top and middle part of the plant. The above results revealed that the pests were found in large number as anymphal stage , on the leaves of plant,in the begining of January, then they complete its life cycle,when the suitable environmental condition was offered .